Economic Growth at the Edge of the Sea: The Political Economy and History of Coastal Fisheries in Indonesia’s 3T Regions (3T: Disadvantaged, Frontier, and Outermost Regions). - Bawias, Ishak; Mozes, Getruida Nita; Puspita, Hery Indria Dwi (Journal of Economic Growth and Development Review, 2025)
This study explores the political economy and historical roots of economic growth in Indonesia’s coastal fisheries, with a focus on the country's 3T regions (disadvantaged, frontier, and outermost). Drawing on qualitative field data and critical policy analysis, the research reveals how historical marginalization, market dependency, legal exclusion, and fragmented governance have shaped uneven development trajectories in these regions. Despite rich marine resources and integration into global seafood markets, small-scale fishers in 3T areas often remain economically insecure and politically invisible. The study highlights how growth has been promoted through centralized, extractive models that prioritize production and capital investment while neglecting community rights and local institutions. However, it also identifies local strategies of resistance, adaptation, and institutional innovation suggesting that endogenous, community-driven growth is possible when socio-political conditions are supportive. By situating fisheries development within a political economy framework, the research calls for a more inclusive and territorially grounded approach to maritime development, one that recognizes coastal communities not as passive beneficiaries, but as central agents in shaping sustainable and just growth. Keywords: Political economy; Coastal fisheries; 3T regions (disadvantaged, frontier, outermost); Marine governance; Inclusive development.